2017
DOI: 10.1016/j.jhin.2016.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patients with hospital-acquired influenza A (H1N1)pdm09 virus admitted to the intensive care unit

Abstract: Influenza A (H1N1)pdm09 infection acquired in the hospital is an independent factor for death in critically ill patients admitted to the ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
4
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 32 publications
3
63
4
6
Order By: Relevance
“…While the mortality of nosocomial cases in the study by Enstone et. al was 26.7% [15], in the study by Álvarez-Lerma et al it was 39.2% [17]; in both studies mortality was notably higher than that due to community-acquired influenza [15,17]. Compared with community-acquired influenza cases, we found a significantly longer stay in patients with nosocomial influenza.…”
Section: Discussioncontrasting
confidence: 38%
See 2 more Smart Citations
“…While the mortality of nosocomial cases in the study by Enstone et. al was 26.7% [15], in the study by Álvarez-Lerma et al it was 39.2% [17]; in both studies mortality was notably higher than that due to community-acquired influenza [15,17]. Compared with community-acquired influenza cases, we found a significantly longer stay in patients with nosocomial influenza.…”
Section: Discussioncontrasting
confidence: 38%
“…Even though vaccination rates were very low in patients with both hospital-acquired and communityacquired influenza virus infection, a higher proportion of nosocomial influenza patients had been vaccinated. This has been observed in other studies [15][16][17] and may be related to the greater number of comorbidities (COPD, diabetes, chronic renal disease, immunodeficiency and chronic cardiovascular disease) for which vaccination is recommended [18].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Recent studies showed that9% of community-acquired pneumonia in Europe is associated with the infection of influenza viruses [2]. Moreover, influenza A (H1N1) pdm09 virus can cause hospital infection, resulting in death in critically ill patients admitted to the intensive care unit [3]. Influenza A/H1N1/pdm 2009 and influenza B viruses may co-infect patients during the epidemic season [4].…”
Section: Introductionmentioning
confidence: 99%
“…The case fatality rate associated with influenza in hospitalised patients remains 3.4-8.3% [1] and may be twice as high when influenza is hospital-acquired (HAI) compared to communityacquired (CAI) [2]. Nosocomial influenza outbreaks lead to increased bed occupancy and closed wards during winter months, with significant financial implications.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%